2015
DOI: 10.21825/vdt.v84i3.16600
|View full text |Cite
|
Sign up to set email alerts
|

Het effect van ketoprofenbehandeling ter preventie van het postpartum dysgalactiasyndroom bij zeugen

Abstract: Postpartum dysgalactia syndrome (PDS) is an economically important condition in sows. The syndrome is characterized by a reduced milk and colostrum production within 12 to 48 hours post partum. The objective of this study was to determine whether preventive treatment with ketoprofen (Ketofen®10%, Merial, Belgium) has a positive effect on the subclinical form of PDS. Sows (n = 39) were randomly divided into two groups: one served as control group whereas the other was treated intramuscularly with ketoprofen wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…The authors concluded that lying passively may be one of the signs of pain and inflammation after parturition in young sows, and when treated with ketoprofen, pain and inflammation can be alleviated and therefore support the health of the dam. This is in line with later studies by Homedes et al (2014) and Claeyé et al (2015). Claeyé et al (2015) showed that healthy sows treated with ketoprofen (1 mg/kg im) within 12 h after parturition had a reduced rectal temperature by 0.43°C.…”
Section: Medical Interventions For Improving Reproductive Health Duri...supporting
confidence: 93%
See 1 more Smart Citation
“…The authors concluded that lying passively may be one of the signs of pain and inflammation after parturition in young sows, and when treated with ketoprofen, pain and inflammation can be alleviated and therefore support the health of the dam. This is in line with later studies by Homedes et al (2014) and Claeyé et al (2015). Claeyé et al (2015) showed that healthy sows treated with ketoprofen (1 mg/kg im) within 12 h after parturition had a reduced rectal temperature by 0.43°C.…”
Section: Medical Interventions For Improving Reproductive Health Duri...supporting
confidence: 93%
“…This is in line with later studies by Homedes et al (2014) and Claeyé et al (2015). Claeyé et al (2015) showed that healthy sows treated with ketoprofen (1 mg/kg im) within 12 h after parturition had a reduced rectal temperature by 0.43°C. Homedes et al (2014) showed that healthy sows treated with ketoprofen (3 mg/kg im) within 12 h after parturition had a lower piglet mortality rate between Days 2 and 7 after farrowing and more piglets weaned per litter.…”
Section: Medical Interventions For Improving Reproductive Health Duri...supporting
confidence: 93%
“…The treated sows presented less constipation and feed refusal during lactation, but there was no effect on the weight gain of piglets from treated sows. This was confirmed by Claeyé et al , 56 who showed that in healthy sows, ketoprofen (1 mg/kg im) reduced rectal temperature by 0.43°C during the first 24 hours. There was no effect on weight gain or survival of the piglets.…”
Section: Parenterally Administered Nsaidssupporting
confidence: 58%
“…In the present study, PDS was mainly defined based on the appearance of the udder during the first 3 days postpartum. Postpartum dysgalactia syndrome is assessed according to the absence or presence of inflammation (reddening and swelling) and/or agalactia of at least one teat of the udder [ 28 ]. Thus, some sows that had high fever without any appearance of udder inflammation were not included.…”
Section: Discussionmentioning
confidence: 99%